1994
DOI: 10.1103/physreva.50.r1984
|View full text |Cite
|
Sign up to set email alerts
|

Field-assisted photodetachment process to observe the ponderomotive shift

Abstract: Two-color photodetachment of a negative ion in the presence of a constant magnetic field is proposed as a process in which to observe the ponderomotive shift. Appropriate calculations are reported of the process under consideration based on a simple one-electron model and with the basic physical parameters well within the experimental state of the art.PACS number(s): 32.80.Rm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

1995
1995
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…It is the aim of this comment to show that when the approximate expression of the S-matrix element quoted by Bivona et al (1994) is correctly treated, cross sections are obtained that are in agreement with the Wigner law, contrary to the affirmation of Robinson. Moreover, it will be shown that the corrections to the wavefunction of the bound state suggested by this last author do not significantly affect the values of the photodetachment cross sections calculated by using the procedure proposed by Bivona et al (1994).…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…It is the aim of this comment to show that when the approximate expression of the S-matrix element quoted by Bivona et al (1994) is correctly treated, cross sections are obtained that are in agreement with the Wigner law, contrary to the affirmation of Robinson. Moreover, it will be shown that the corrections to the wavefunction of the bound state suggested by this last author do not significantly affect the values of the photodetachment cross sections calculated by using the procedure proposed by Bivona et al (1994).…”
mentioning
confidence: 83%
“…It is the aim of this comment to show that when the approximate expression of the S-matrix element quoted by Bivona et al (1994) is correctly treated, cross sections are obtained that are in agreement with the Wigner law, contrary to the affirmation of Robinson. Moreover, it will be shown that the corrections to the wavefunction of the bound state suggested by this last author do not significantly affect the values of the photodetachment cross sections calculated by using the procedure proposed by Bivona et al (1994). In the E-gauge the exact expression of the S-matrix that describes the photodetachment event is given by where i is the wavefunction of the electron interacting with both the static potential V (r) and the radiation field, which tends to the bound bare state i (r, t) when the radiation field is turned off, and f is the wavefunction describing the free electron driven by the electromagnetic field.…”
mentioning
confidence: 83%
See 3 more Smart Citations